Country size and public administration - Jugl, Marlene (Cambridge : Cambridge University Press, 2022)
Although countries differ tremendously in population size, comparative public administration has not considered this context factor systematically. This Element provides the most comprehensive theoretical and empirical account to date of the effects that country size has on the functioning of public administration. It synthesizes existing literature and develops a theoretical framework that distinguishes the effects of small, medium and large country size on administrative structures, practices, and public service performance. Large states with larger administrations benefit from specialization but are prone to coordination problems, whereas small states experience advantages and disadvantages linked to multifunctionalism and informal practices. Midsize countries may achieve economies of scale while avoiding diseconomies of excessive size, which potentially allows for highest performance. Descriptive and causal statistical analyses of worldwide indicators and a qualitative comparison of three countries, Luxembourg, the Netherlands and Germany, demonstrate the various ways in which size matters for public administrations around the world.
Title from publisher's bibliographic system (viewed on 10 Jun 2022).
Keywords: Public administration; Economies of scale; States, Size of